Employment transitions in 13 European countries: Levels, distributions and determining factors of net replacement rates - Herwig Immervoll; Cathal O'Donoghue (University of Essex, Institute for Social and Economic Research (ISER), 2003)
This paper utilises a multi-country microsimulation tax-benefit model for Europe, EUROMOD, to simulate the distribution of net replacement rates for 13 European countries. We look at different types of labour market transitions by comparing household incomes in the current state with simulated in-work/out-of-work counterfactuals. In particular we compare how the importance of household composition and different income sources varies across countries and for different replacement rate bands. We also show which individual and household characteristics are associated with observed replacement rate levels.
Keywords: H31; J65; E60; C81; 330; Net Replacement Rate; Unemployment Benefits; Work Incentives; European Union; Microsimulation; Arbeitsmobilität; Arbeitslosigkeit; Erwerbsverlauf; Lohnersatzleistungen; Arbeitslosenversicherung; Ökonomischer Anreiz; Arbeitsangebot; EU-Staaten